A secure image authentication algorithm with pixel-level tamper localization - Jinhai Wu; Zhu, B.B.; Shipeng Li; Fuzong Lin (2004 International Conference on Image Processing, 2004. ICIP '04, 2004)
In this paper, we use a generalized model for all the previously proposed pixel-wise authentication schemes. Then we show how this model can be compromised with an Oracle attack. This motivated us to develop a novel authentication scheme to be described here. The new scheme is designed to detect any changes to a signal. It consists of two mechanisms dedicated to authenticity verification for a signal and localization of tampered pixels, respectively. The scheme is secure yet it maintains the fine tamper localization capability of a pixel-wise scheme. Experimental results show that the proposed scheme has a good accuracy in locating tampered pixels.